Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

solve for x and y

x + 10 = 2y - 3​


Sagot :

Answer:

y=13

Step-by-step explanation:

Simplifying y + 10 = 2y + -3 Reorder the terms: 10 + y = 2y + -3 Reorder the terms: 10 + y = -3 + 2y Solving 10 + y = -3 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 10 + y + -2y = -3 + 2y + -2y Combine like terms: y + -2y = -1y 10 + -1y = -3 + 2y + -2y Combine like terms: 2y + -2y = 0 10 + -1y = -3 + 0 10 + -1y = -3 Add '-10' to each side of the equation. 10 + -10 + -1y = -3 + -10 Combine like terms: 10 + -10 = 0 0 + -1y = -3 + -10 -1y = -3 + -10 Combine like terms: -3 + -10 = -13 -1y = -13 Divide each side by '-1'. y = 13 Simplifying y = 13